2023
DOI: 10.3390/nu15030758
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Genomic Predictors of Sarcopenia and Sarcopenic Obesity Using UK Biobank Data

Abstract: The substantial decline in skeletal muscle mass, strength, and gait speed is a sign of severe sarcopenia, which may partly depend on genetic risk factors. So far, hundreds of genome-wide significant single nucleotide polymorphisms (SNPs) associated with handgrip strength, lean mass and walking pace have been identified in the UK Biobank cohort; however, their pleiotropic effects on all three phenotypes have not been investigated. By combining summary statistics of genome-wide association studies (GWAS) of hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…In addition, obesity causes fat accumulation in the muscles, which may promote insulin resistance, oxidative stress, and pro-inflammatory responses in overweight and obese populations, leading to sarcopenia [ 3 ]. Factors such as body fat, grip strength, muscle mass, and gait speed, which affect the occurrence of SO, may be partially influenced by genetics as well as aging [ 4 ]. Hence, SO can occur not only in the elderly but also in people with related genes, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, obesity causes fat accumulation in the muscles, which may promote insulin resistance, oxidative stress, and pro-inflammatory responses in overweight and obese populations, leading to sarcopenia [ 3 ]. Factors such as body fat, grip strength, muscle mass, and gait speed, which affect the occurrence of SO, may be partially influenced by genetics as well as aging [ 4 ]. Hence, SO can occur not only in the elderly but also in people with related genes, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that the AGRN rs4074992 C allele was significantly over-represented in Turkish sprint/power athletes compared to endurance athletes and was associated with a greater CSA of fast-twitch muscle fibers in physically active Russian individuals. Muscle fiber size is a surrogate indicator of muscle mass and is positively associated with power and strength [ 42 , 43 , 44 ]. According to the GTEx portal [ 32 ], the AGRN rs4074992 (intergenic variant) is significantly ( p ≥ 3.8 × 10 −8 ) associated with altered expression of the AGRN gene in multiple tissues.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are other predictors of sarcopenia not included in our study, such as genomic predictors. Genomic predictors of sarcopenia based on previously discovered genome-wide significant SNPs, associated with handgrip strength, appendicular lean mass, and walking pace, have been described [66]. Finally, the study participants were selected from four teaching centers in Spain that are relatively close to one another, thus potentially restricting the generalizability of our findings to areas outside Spain.…”
Section: Discussionmentioning
confidence: 99%